Experimental evidence of interhemispheric transport from airborne carbon monoxide measurements - Newell, R. E.; Gauntner, D. J. (1979)
During the period 28-30 October 1977, a Pan American 747-SP aircraft flew around the world with an automated instrument package that included measurements of atmospheric CO made every 4 sec. The flight path extended from San Francisco, over the North Pole to London, south to Capetown, over the South Pole to Auckland, and back to San Francisco. The data collected show large changes with longitude, which are interpreted as direct evidence of interhemispheric mixing. Possible sources for CO are discussed.